Proposed Amendment on the Reform of the IMF Executive Board and Fourteenth General Review of Quotas : Status of Acceptances and Consents. (Policy Papers; Policy Paper ;, 2013)
This status report reviews progress toward implementation of the 2010 Quota and Governance Reforms. It updates the status of consents to the proposed quota increases under the 14th General Review of Quotas and of acceptances of the Proposed Seventh Amendment on the Reform of the Executive Board ('Board Reform Amendment' or 'Seventh Amendment') as set out in the Board of Governors Resolution No. 66-2.